The warmth of other suns [compact disc, unabridged] : the epic story of America's great migration - Wilkerson, Isabel (Brilliance Audio on compact disc., 2011)
An epic history covering the period from the end of World War I through the 1970s chronicles the decades-long migration of African Americans from the South to the North and West through the stories of three individuals and their families.